Signals Controlling Lytic Granule Polarization at the Cytotoxic Immune Synapse - Kabanova, Anna; Zurli, Vanessa; Baldari, Cosima Tatiana (Frontiers in Immunology, 2018)
Cytotoxic immunity relies on specialized effector T cells, the cytotoxic T cells, which are endowed with specialized cytolytic machinery that permits them to induce death of their targets. Upon recognition of a target cell, cytotoxic T cells form a lytic immune synapse, and by docking the microtubule-organizing center at the synaptic membrane get prepared to deliver a lethal hit of enzymes contained in lytic granules. New insights suggest that the directionality of lytic granule trafficking along the microtubules represents a fine means to tune the functional outcome of the encounter between a T cell and its target. Thus, mechanisms regulating the directionality of granule transport may have a major impact in settings characterized by evasion from the cytotoxic response, such as chronic infection and cancer. Here, we review our current knowledge on the signaling pathways implicated in the polarized trafficking at the immune synapse of cytotoxic T cells, complementing it with information on the regulation of this process in natural killer cells. Furthermore, we highlight some of the parameters which we consider critical in studying the polarized trafficking of lytic granules, including the use of freshly isolated cytotoxic T cells, and discuss some of the major open questions.